Energy Evaluation and Economic Impact Analysis of Green Roofs Applied to a Pilot Region in Aegean Coast of Turkey - Serdar Çelik; William Retzlaff; Susan Morgan; Ayla Oğuş Binatlı; Cemil Ceylan (Izmir University of Economics, Department of Economics, 2010)
This paper examines the energy savings, environmental benefits, and economic impact of green roof systems applied to a "micro" region in Western Turkey. This subdivision (Artur) in Karaaægaç, Izmir, consists of 1729 residential units, mostly used as summer homes. The units are in 45m2, 60m2, 90m2, and 105m2 sizes. Five different plant types were considered to be blended and planted in two different choices of growth media. Thermal benefits of the vegetated roofs to the pilot site were evaluated using appropriate heat transfer equations. For analyzing the impact of use of such systems on the local economy, monetary injection into the local economy was calculated and a multiplier effect of 2.66 was assumed. Net present value (NPV) of the generated income for the first 10 years was calculated to be approximately 14.5 million. In addition, approximately 300 new local jobs over a period of 10 years were estimated to be created.
Keywords: Q2; Q4; Q5; 330; Green roofs; Economic impact; Energy conservation; Turkey; Nachhaltiges Bauen; Energieeinsparung; Umweltschutz; Wirkungsanalyse; Ägäis; Türkei